Gestão de recursos financeiros no setor educacional: uma análise das escolas da rede estadual de Pernambuco - Santos, Maria Auxiliadora Gomes (2010)
The dissertation which is now being presented aims to identify whether those directive principIes and guidelines for a new public management have been adopted specially on the management for financiaI resources which have been transferred to public schools. A theoretical-conceptual survey on the state reforming process for developing research has been made as well as both the official data on public [mancial administration and students' proficiency from Public Schools in the State of Pernambuco have been duly consulted. It has not been identified in the present study a significant relationship between the values transferred to the schools and the variation on students' proficiency from those schools studied. The result of such a job points towards a direction in which is still extremely low the introduction of managerial model practices, into the field of managing public resources for education, that results in delays for transferring financiaI resources owed to public schools. In order to reverting such a situation it is needed to split off traditional models for managing public resources, as well as introducing a new management culture which allows for acting quickly and efficiently on the part of different actors involved in this activity. The introduction of managerial practices extracted from private management, as it has been recommended by the new public management, might be a good way.